ANALISIS PEMILIHAN LOKASI PEMASANGAN REKLAME DI WILAYAH DKI JAKARTA. (Studi Kasus pada PT Prisma Harapan) - Pritta Aprilia Hapsari; Bulan Prabawani; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
Outdoor advertising media or commonly called billboards is one that widely used in the media to promote a product or service updates. In the process of selecting the location of the billboard there are several factors that affect, the internal factors relating to advertising agencies and external factors that have a connection with consumers and the local government. Based on the existing problems are suspected factors influence internal and external factors on site selection and installation of billboards in Jakarta.Type of this research is exploratory, the data collection method is study of literature, observation, and in-depth interviews with qualitative data analysis techniques. The results showed that internal factors are derived from advertising agencies do not have a significant influence on the selection of the location of the installation of billboards. However, external factors relating to consumers and the local government have a significant influence on the process of selecting the location of installation of billboards in Jakarta. Recommended for advertising agencies as the organizers of advertisement should be more sensitive to the changes that occur, because advertising activities fluctuated, advertising agencies should also increase the professionalism of the performance so that advertising agencies do not apply be stakeholders, but also a partner for the local government and the public, advertising agencies are should not only thought of profitable by always displaying commercial advertisements. However, it should undertake the installation of non-commercial billboard advertising as a form of social responsibility provided by advertising agencies to the people of Jakarta.